The Diagnosis and Management of the Acute Abdomen in Pregnancy (Springer International Publishing, 2018)
This text is intended to serve as a reference guide for clinicians who consult pregnant women presenting with abdominal and pelvic pain. Many health care providers care for pregnant women including attending physicians, resident physicians, advanced practice nurses, certified nurse mid-wives, labor and delivery nurses, operating room and post-anesthesia care nurses, medical students and others. The book addresses obstetrical and non-obstetrical aspects to the diagnostic process. Key features include: • the anatomical and physiological alterations of pregnancy • physical examination and management challenges in the first, second and third trimesters • laboratory findings • diagnostic imaging • assessment of the fetus(es) • Surgical and anesthetic issues • Medico-legal challenges • Perinatal and neonatal issues The Diagnosis and Management of the Acute Abdomen in Pregnancy will serve practitioners as a quick-reference guide to those who encounter pregnant women in pain.